2015
DOI: 10.1111/ejn.12822
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a direct GABAergic pallidocortical pathway in rodents

Abstract: The basal ganglia, interacting with the cortex, play a critical role in a range of behaviors. Output from the basal ganglia to the cortex is thought to relay through the thalamus, yet an intriguing alternative is that the basal ganglia may directly project to, and communicate with, the cortex. We explored an efferent projection from the globus pallidus externa (GPe), a key hub in the basal ganglia system, to the cortex of rats and mice. Anterograde and retrograde tracing revealed projections to the frontal pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 30 publications
1
73
0
Order By: Relevance
“…For example, dopamine from the SNc acting on D 2 receptors in the striatum enhances GPe activity and promotes sleep (Qiu et al, 2014). We propose that pallidocortical projections regulate sleep (Chen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, dopamine from the SNc acting on D 2 receptors in the striatum enhances GPe activity and promotes sleep (Qiu et al, 2014). We propose that pallidocortical projections regulate sleep (Chen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The GPe is a key basal ganglia hub and also directly interacts with the cortex, and we hypothesize that DBS in the GPi and STN may act through the GPe for the regulation of sleep and motor behavior (Qiu et al, 2010, Qiu et al, 2014, Chen et al, 2015). GPe lesions can produce or exacerbate both motor and non-motor symptoms of Parkinson’s disease, including sleep dysfunction, while lesions to other basal ganglia output pathways like the SNr or thalamus have minimal effects on sleep in rats (Zhang et al, 2006, Qiu et al, 2010, Fuller et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence continues to support the notion of functional antagonism between these pathways (Freeze et al, 2013; Kravitz et al, 2010; Schmidt et al, 2013), additional anatomical and functional studies have identified unanticipated circuit connectivity in both the SNr and GPe (among other basal ganglia nuclei). Recent examples in the GPe include the identification of a pallidocortical projection that entirely bypasses thalamic relays to modulate frontal cortex (Chen et al, 2015; Saunders et al, 2015), as well as pallidostriatal innervation by so-called “arkypallidal” GPe neurons (Abdi et al, 2015; Mallet et al, 2012). The SNr, generally conceptualized as an inhibitory nucleus, contains a subset of glutamatergic neurons recently mapped to innervate and excite the reticular thalamus, a higher-order non-relay region (Dunn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The GPe projects to virtually all of the basal ganglia components, including the striatum (Mallet et al, 2012). Interestingly, direct GABAergic connections with the cortex have been recently described (Chen et al, 2015;Saunders et al, 2015). Therefore, the GPe may play an integrative role coordinating neuronal activity across the basal ganglia with direct links with the cortex.…”
Section: Introductionmentioning
confidence: 99%